Autocatalytic symmetry breaking and chiral amplification in a feedback network combining amino acid synthesis and ligation - Paul G. Higgs; Donna G. Blackmond (Proceedings of the National Academy of Sciences, 2025)
A kinetic model coupling prebiotically plausible synthesis of enantioenriched proteinogenic amino acids with catalytic peptide ligation leads to an autocatalytic network that may exhibit symmetry breaking and chiral amplification, providing a feasible route to the emergence of biological homochirality. We show that symmetry breaking leading to chiral amplification can occur in two ways: a constructive mechanism in which dimers catalyze the synthesis of monomers of the same enantiomer, and a destructive mechanism in which dimers catalyze the breakdown of monomers of the opposite enantiomer.